Harvesting index and ratio of grain and non-grain part of a head of spring durum wheat varieties in the West Siberia - M. G. Evdokimov; V. S. Yusov (Зерновое хозяйство России, 2018)
Harvesting index and ratio of grain and non-grain part of a head of spring durum wheat varieties in the West Siberia The varieties of spring durum wheat ‘Omskaya yantarnaya’, ‘Omsky korund’, ‘Zhemchuzhina Sibiri’, ‘Omsky izumrud’, ‘Omskaya stepnaya’, ‘Omsky tsirkon’ were studied in the conditions of the years 2013-2015. There was established a harvesting index, a share of non-grain part of a head (awnings, spikelets and floral scales, a spike stem) and their ratio with grain part. The harvesting index (taking into consideration lateral shoots varied from 30.8% (‘Omsky tsirkon’) to 39.9% (‘Omsky izumrud’). The main part of a head belongs to grain amount (71.6%-77.5%). Non-grain part (capes) is of 22.5-28.4%. The most part of non-grain mass belongs to scales (‘Omsky tsirkon’ with 12.9% and ‘Zhemchuzhina Sibiri’ with 15.7%). The average value of the share of awns in all varieties does not exceed 9.3%, with fluctuations of 6.9% (‘Omsky tsirkon’) to 10.3% (‘Omskaya stepnaya’). The share of a spike stem is small (2.6-3.1%). In the structure of the main sprout of durum wheat varieties, the proportion of awns is of 2.8-5.0%, the proportion of a spike stem is of 1.1-1.7%, the proportion of scales is of 5.1-7.8%. Non-grain elements of a spike are about 12.3% on average, with fluctuations from 9.0% (‘Omsky tsirkon’) to 14.1% (‘Zhemchuzhina Sibiri’). The share of grain amount of the whole sprout is of 47.8% in ‘Omsky izumrud’ and 38.7% in ‘Omsky tsirkon’. The ratio of a share of a spike to a straw of the main sprout is as follows: ‘Omsky izumrud’ 1.59/1.0; ‘Zhemchuzhina Sibiri’ 1.35/1.0; ‘Omskaya stepnaya’ and ‘Omskaya yantarnaya’ 1.24/1.0; ‘Omsky tsirkon’ 0.91/1.0 and ‘Omsky korund’ 1.11/1.0.